Shear layer response to overmodulated acoustic perturbations - Nicholls, CJ; Chakravarthy, K; Tang, BMT; Williams, B; Bacic, M (AIP Publishing, 2023)
Shear layers act as demodulators when subjected to amplitude modulated, acoustic perturbations. Recent work explained that the demodulation is a result of the hypothesized relationship between the excitation waveform and the vorticity signal of the large-scale structures, which was represented by a half-wave rectification model. In this paper, this model is explored by overmodulating the excitation signal amplitude. The rectifier model predicts several effects of overmodulation on the flow response, including a doubling of the demodulated response frequency. To validate these predictions, a free, round jet that is excited acoustically upstream of the nozzle is studied using particle image velocimetry. Analytical results from the model are confirmed using a second experimental setup where a jet that emerges from a nozzle and attaches to an adjacent, inclined wall is excited acoustically. Beyond the insight it provides into shear layer vortex dynamics, overmodulation serves as a useful excitation technique for practical applications, where the shear layer response frequency can be increased at the expense of the response amplitude.